Application of Humanistic Existential Positive Basic Dimensions in Meeting the Psychological Needs of Self-Injury Perpetrators - Erna Agustina Yudiati; Dwi Yuwono Puji Sugiharto; Edy Purwanto; Sunawan Sunawan (International Conference on Science, Education, and Technology, 2022)
Abstrak. The causes of someone committing self-injury are lack of self-love, lack of ability to think about the impact of the actions taken, lack of understanding of emotional changes, lack of self-confidence to change for the better, and other alternatives in solving a problem. That requires intervention that can meet these psychological needs. The research's purpose is to know the impact of the application on the Basic Dimensions of Positive Existential-Humanistic in Fulfilling the Psychological Needs of Self-Injury Actors. The method used in this research is Pre-Experimental Design. Research subjects: five teenagers or adults who did self-injury, female, 16-21 years old. The results of this study are: There is an effect of applying positive basic dimensions in the Humanistic Extension intervention in fulfilling the psychological needs of self-injury perpetrators. When the intervention is given by focusing more on the positive basic dimensions of the human being, the Need for Attachment, the need for Control or Orientation, the need for Pleasure/Pain Avoidance, and the need for Self-Enhancement will be met.